Tournament Incentives in the Field: Gender Differences in the Workplace - Delfgaauw, Josse; Dur, Robert; Sol, Joeri; Verbeke, Willem (Journal of Labor Economics, 2013)
We ran a field experiment in a Dutch retail chain consisting of 128 stores. In a random sample of these stores, we introduced short-term sales competitions among subsets of stores. We find that sales competitions have a large effect on sales growth, but only in stores where the store’s manager and a sufficiently large fraction of the employees have the same gender. Remarkably, results are alike for sales competitions with and without monetary rewards, suggesting a high symbolic value of winning a tournament.